Tracking the Deadlock of the Struggle on Inclusive Citizenship Study of the Disability Movement in DIY Province - Isnenningtyas Yulianti (Jurnal Studi Sosial dan Politik, 2020)
Abstract Inclusive citizenship is currently being fought for by groups that care about vulnerable groups. In Indonesia the ideals of inclusive citizenship are also fought for persons with disabilities. So far, persons with disabilities have become excluded social groups. The disability movement is intensely voicing inclusive citizenship through the struggle to form regulations that can bring changes to the lives of persons with disabilities, starting from the CRPD Convention, the Disability Persons Act, then local regulation of Disabilities. This paper will use the concept of structuration Giddens and confronting the disability movement in fighting for inclusive citizenship with efforts from the government to capture the issue of inclusive citizenship. The Disability Movement in Yogyakarta Province is a model of the movement that has succeeded in fighting for regional regulations for persons with disabilities. This movement was considered successful when the national movement struggled for the Law on Persons with Disabilities experiencing a deadlock, but in the process the disability movement has not been able to process the issue of inclusive citizenship in its struggle, and the local government as if it does not understand what the disability movement is trying to achieve. Instead of make realize the ideals of inclusive citizenship, the Disability Movement is trapped in an exclusive movement model. The Movement Model in DIY Province is an example in the struggle for inclusive citizenship which was initially considered successful but later suffered a deadlock.